AB0991 Osteoporosis and fractures in patients with cirrhosis. can frax be useful for screening?. (12th June 2018) - Casado, E.; Arévalo, M.; Profitós, J.; Lira, A.; Del Río, L.; Valero, O.; Larrosa, M.; Sánchez-Delgado, J.; Gratacós, J.
Abstract : Background: Osteoporotic fractures are a serious complication in patients with cirrhosis. In addition to the high morbidity and mortality of the patients who suffer them, fragility fractures represent a high cost for Healthcare systems. However, there are very few studies that evaluate the prevalence of osteoporosis and fractures in patients with liver cirrhosis different than primary biliary cirrhosis (non-PBC cirrhosis). There are also no clinical guidelines with recommendations for osteoporosis screening in these patients. Objectives: To assess the prevalence of osteoporosis and fragility fractures in patients with non-PBC cirrhosis in our environment, and the associated risk factors. To analyse if the FRAX tool can be useful in the diagnostic screening of these patients. Methods: From November 2015 to September 2017, outpatients older than 40 years diagnosed with non-PBC cirrhosis (any Child stage) were randomly included. Demographic, clinical and analytical data (calcium, phosphorus, 25-hydroxyvitamin D and PTH) were collected from all patients. A bone densitometry, GE, Lunar Prodigy (DXA) and vertebral fracture assessment (VFA) were also performed, for the diagnosis of osteoporosis (T-score ≤−2.5), and vertebral fracture. The 10 year absolute fracture risk was calculated using FRAX (https://www.sheffield.ac.uk/FRAX/tool.aspx?country=4). A descriptive statistic of the main variables was carried out, with univariate and multivariate analysis to assess which predictive factors could be related to the presence of osteoporosis and/or fragility fractures. Results: Ninety-two patients were included (71% male and 29% female). Age 63±11 years. The etiology of cirrhosis was: alcohol (52%), hepatitis C virus (27%) and alcohol +hepatitis C virus (9%). Stage: Child A (80.4%), B (17.4%) and C (2.2%). Mean 25-hydroxyvitamin D was 18.5±9.8 ng/ml and PTH 51.8±23.0 pg/ml. 16 patients (17%) had osteoporosis by DXA, 54 patients (59%) osteopenia and 22 (24%) had a normal bone mineral density (BMD). 8 patients (9%) had suffered some fragility fracture (vertebral fracture in 6 cases). The 10 year absolute risk for major fracture (vertebra, humerus, femur or radius) by FRAX without BMD was 5.7±4.5; and with BMD 4.7±4.9. Age and female sex were associated with the presence of osteoporosis, and a BMI higher than 30 was found to be a protective factor. A BMD in the range of osteoporosis was the only factor associated with fracture. FRAX for major fracture without BMD higher than 6.6% in this population had a high sensitivity (69%) and specificity (85%) for the diagnosis of osteoporosis, which implies a negative predictive value of 93%. Using this FRAX cut-off for indicating DXA in cirrhotic patients could expect a saving of 76% of DXA scans. Conclusions: The prevalence of osteoporosis and fractures in patients with non-PBC cirrhosis, even in mild stages, is higher than in the healthy population, being more frequent in women and older patients. The FRAX tool can be useful in the selection of patients with cirrhosis to be assessed by a bone densitometry. Disclosure of Interest: None declared